STRATEGI EFEKTIF DALAM MENGAJARKAN SASTRA UNTUK PENDIDIKAN TINGGI - Siska Amelia Maldin (Journal Of Language Education and Development (JLed), 2021)
Literature and culture are two elements that cannot be separated as overall general knowledge. Thus, it is evident that EFL learners are suggested to learn literature and study it when learning English as a foreign language. This is due to the reason that literature can be used as motivating material that is represented in the value listed in the story. Clearly, literature is able to provide EFL students access to other people whose language they are studying. Unfortunately, research shows that teachers in high school find it difficult and seems boring to teach literature in the EFL classroom. Thus, this paper is aimed to show several strategies that EFL teachers might use to teach literature in their classroom as part of a genre-based approach application. The strategies are divided into pre-activity, whilst-activity, and post-activity.